THE EFFECT OF RICE FIELD AREA, LAND OWNERSHIP STATUS, AND RELIGIOSITY ON RICE FARMERS’ INCOME IN PUJON DISTRICT - Akbar, Muhammad Fikri; Fawwaz, Muhammad Iqbal (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2022)
Pujon District is one of the areas where most of the population relies on making a living from the agricultural sector. In the Pujon District area, the average farmer with a land area of less than hectare with the amount of production that can be produced is 1-3 tons of rice. However, based on the phenomenon of the level of income of farmers in Pujon District, there are factors that influence it, such as rice field area, land ownership status, and religiosity. This study aims to examine the effect of rice field area, land ownership status, and religiosity on the income of rice farmers in Pujon District. This study conducted in the field in order to obtain information or data needed in research regarding respondents' responses by using questionnaires. The technique used in this research is random sampling technique is a technique of taking samples from respondents randomly. This questionnaire was then distributed to all residents of Pujon District and a sample of 109 respondents was obtained for distribution, using the slovin formula. The findings reveal that, the land area partially has a positive and significant effect on the income of rice farmers in Pujon District. Likewise, the land ownership status partially has a positive and significant effect on the income of rice farmers. Meanwhile, religiosity partially has no effect on the income of rice farmers. Furthermore, the land area, land ownership status, and religiosity simultaneously have a significant effect on the income of rice farmers in Pujon District.